Morality In George Bernard Shaw's Man and Superman Drama (1903): A Sociological Approach - MAHARANI, KARLINDA DEVI (2012)
The problem of the study is how the morality in the late nineteenth century reflected in George Bernard Shaw's Man and Superman. The objective of the study is to analyze the drama based on the structural element and based on the sociological perspective. The method of data collection is qualitative method. This study uses two data sources, namely primary and secondary data sources. The primary data source is the script of the play itself, while the secondary data source includes books and other data that have relationship with the research. Technique of the Data Collection is note taking, while the technique of Data Analysis in this study is descriptive and hermeneutic. Based on the structural analysis, it is evident that in Man and Superman, Shaw wants to convey a message that "the higher the man's moral, the more respectable he is". Based on the sociological analysis, Shaw in Man and Superman wants to reflect the social condition of upper class in England in the late nineteenth century.